The Role Of Digital Marketing As A Promotional Media Towards Increasing Insurance Product Purchases: A Case Study Of PT. Asuransi Allianz Life Indonesia - Jessica Anastasia; Irwan Tanamas; Deviari Damalita Soemarno; Arvy N. Osma (Digital Innovation : International Journal of Management, 2025)
The rapid advancement of digital technology has transformed marketing strategies in various industries, including insurance. Digital marketing plays a crucial role in increasing brand awareness, attracting potential customers, and influencing purchasing decisions. This study aims to explore the role of digital marketing as a promotional tool in enhancing the purchase of insurance products at PT. Asuransi Allianz Life Indonesia using a qualitative approach.This research adopts a qualitative methodology with a case study approach. Data collection was conducted through in-depth interviews with key informants (Chief Account Officer Allianz) and insurance agents at Allianz Life Indonesia. Additionally, document analysis and observations of the company’s digital marketing strategies were used to gain comprehensive insights. The collected data were analyzed using thematic analysis to identify patterns and key themes related to the effectiveness of digital marketing in influencing customer decisions.The findings reveal that digital marketing plays a significant role in shaping customer perceptions and purchasing decisions. Social media engagement, personalized content, and interactive customer communication are key factors in building trust and increasing customer interest in insurance products. Moreover, challenges such as digital competition, data privacy concerns, and customer skepticism towards online promotions were identified as barriers that need to be addressed to enhance digital marketing effectiveness.The study implies that insurance companies should continuously adapt their digital marketing strategies by leveraging data analytics, improving customer interaction, and providing transparent and informative content. By strengthening these aspects, digital marketing can serve as a powerful tool to enhance competitiveness and sustain growth in the insurance industry within the digital era.